"No Time to Rearrange the Furniture in the Living Room": Current Debates in Urban Conservation in the Global South. (2nd January 2021) - Cheong, Caroline S.
ABSTRACT: The synchronicity of urban decline and heritage in Global South historic cities presents significant challenges for public, private and third sector actors. Though development and planning communities increasingly recognize heritage's role in creating sustainable cities and thriving communities, many lack the will, capacity or knowledge of how to capitalize upon this hybridity. In assessing the emergent literature around the particularities of urban conservation and regeneration in the Global South, this article interrogates conservation responses from the public, private and third sectors. Firstly, it problematizes development banks' predominance in responding – and publishing their responses – to these challenges. The article further questions the efficacy of prevailing, material-centered conservation approaches favored by local governments, thereby prioritizing social outcomes over material ones. The article concludes by presenting new avenues of interdisciplinary and transnational inquiry that merge planners' and heritage specialists' expertise, paying particular attention to financial and policy tools that advance an equitable form of heritage-led regeneration.